Finite element modeling of flexural behavior of reinforced concrete beams externally strengthened with CFRP sheets (Fracture and Structural Integrity, 2021)
In this research, the finite element method is used to develop a numerical model to analyse the effect of the external strengthening of reinforced concrete beams by using carbon Fiber Reinforced Polymer (CFRP) sheets. A finite element model has been developed to investigate the behavior of RC beams strengthened with CFRP sheets by testing nineteen externally simple R.C. beams, tested under a four-point load setup until failure. Various CFRP systems were used to strengthen the specimens.  The numerical results using the (ANSYS workbench v.19.1) were calibrated and validated with the experimental results.  The research results indicate a significant improvement in the structural behavior of the specimens strengthened using CFRP sheet systems. Then the validated model investigated the effect of the width of CFRP sheets, no of layers, and CFRP size on the behavior of strengthened R.C. beams. Results of this numerical investigation show the effectiveness of increase CFRP width to improve the flexural capacity of R.C. beams. An increase in the flexural capacity up to 100 % compared to the control beam.
Keywords: Strengthening; Carbon fiber reinforced polymer; Deflection; ANSYS; Ultimate strength